THE UNRECORDED IDIOMATIC EXPRESSION OF LIO TRIBE IN FLORES ISLAND - Maria Asriana Nenu; Darmawan Darmawan; Nur Syamsiyah Ekhsan (Universitas Negeri Islam Sumatera Utara, 2024)
This research aims (1) to identify idiomatic expression used in traditional ceremonies (2) classifying the types of idiomatic expression, (3) and determining the most dominant of idiomatic expression, and (4) interpreting the meaning of idiomatic expression in traditional ceremonies of Lio tribe. The result of the research related to identify idiomatic expression used in traditional ceremonies shows that there are 15 idiomatic expressions used in the marriage ceremony, 3 idiomatic expressions used in the birth ceremony, and there are 5 idiomatic expressions in death ceremony. The result of classifying the types of idiomatic expression shows that there are 8 types of idiomatic expressions in the four ceremonies. The type of simile appear 4 times, the type of binomials appear 1 time, the type of trinomialas appear 3 times, the type of proverbs appear 1 time, the type of eupiesms appear 11 times, the type of appear cliche 2 time, the type of fix statements appear 4 times and the last one is the type of other language appears 1 time. The results showed that the most common idiomatic expressions are eupisem which appear 11 times. The meaning of idiomatic expressions was translated based on lexical meaning, grammatical meaning, and idiomatic meaning.